A mild capping method for SPPS on the N-methyl diaminobenzoyl linker: Synthesis of an N-acyl urea appended C. elegans neuropeptide. Issue 44 (31st October 2018) - Arbour, Christine A.; Stockdill, Jennifer L.
Graphical abstract: Highlights: Mild carbodiimide activation avoids acylation of hindered amine on linker. Efficient N -terminal capping achieved with mild activation. 76% of MeDbz linker experiences acylation with 5 treatments of acetic anhydride. 0% of MeDbz linker experiences acylation with 5 treatments of benzoic acid with DCC activation. Abstract: In this manuscript, we establish the susceptibility of the N -methyldiaminobenzoyl linker to undergo undesired acylation during standard peptide capping with acetic anhydride. Successive capping treatments led to problematic levels of linker incapacitation. We describe a mild, inexpensive alternative capping strategy that is completely selective for the N terminus with no acylation of the linker detected for any of the substrates evaluated. The utility of this protocol is demonstrated via the synthesis of the CAPA-PVK-1 consensus sequence of the C. elegans neuropeptide-like protein precursor peptide NLP-44.